PENGUKURAN SEMANTIC SIMILARITY PADA GEN PFCRT DAN DHFR BERBASIS ONTOLOGY - Dinar Munggaran Akhmad; Siska Andriani (Universitas Teknokrat Indonesia, 2023)
One of the obstacles in the treatment of malaria caused by Plasmodium falciparum is the existence of resistance to antimalarial drugs including chloroquine and sulfadoxine-phyrimethamine. Genes known to be resistant to chloroquine are P. falciparum chloroquine resistance (pfcrt) while Dihydrofolate reductase (dhfr) is resistant to sulfadoxinephyrimethamine. One way to trace gene information is through Gene Ontology by calculating its semantically similarity through Wang's path length approach. The value of similarity between the pfcrt and dhfr genes was tested for the three components in Gene Ontology using Wang's method for Ontology documents. The results showed that the highest similarity value was in the Cellular Component of 0.565, because it has similarities in several components such as the Endoplasmic Reticulum and Cytoplasm. Thus this study is expected to provide initial information regarding resistance and can detect other genes that indicate resistance before further molecular research.